Adaptive solution of PDE-constrained optimal control problems - Rannacher, Rolf (Recent progress in scientific computing, 2007)
The efficient numerical solution of optimal control problems governed by PDEs requires work reduction by adaptive discretization and, in the nonstationary case, storage reduction by checkpointing techniques. This article explains the principles underlying these approaches and illustrates them by examples.